2019
DOI: 10.1017/s144678871900020x
|View full text |Cite
|
Sign up to set email alerts
|

Simplicity and Chain Conditions for Ultragraph Leavitt Path Algebras via Partial Skew Group Ring Theory

Abstract: We realize Leavitt ultragraph path algebras as partial skew group rings. Using this realization we characterize artinian ultragraph path algebras and give simplicity criteria for these algebras. MSC[2010]: 16S35, 16S99, 16P20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…Remark 4.3 The above branching system can also be seen as a partial action of the free group on the edges of the ultragraph and be used to realized L R (G) as a partial skew group ring, see [8,22,24].…”
Section: Branching Systemsmentioning
confidence: 99%
“…Remark 4.3 The above branching system can also be seen as a partial action of the free group on the edges of the ultragraph and be used to realized L R (G) as a partial skew group ring, see [8,22,24].…”
Section: Branching Systemsmentioning
confidence: 99%
“…More recent C * and topological advances include the groupoid approach to the enveloping C * -algebras associated to partial actions of countable discrete groups on (locally) compact spaces in [156], the use of inverse semigroup expansions to treat C *crossed products by twisted partial actions via twisted global actions of the expansion in [68], the full (respectively, reduced) partial C * -crossed product descriptions of full (respectively, reduced) C * -algebras of countable E-unitary or strongly 0-E-unitary inverse semigroups as well as of tight groupoids of countable strongly 0-E-unitary inverse semigroups in [235], the study of the continuous orbit equivalence for partial dynamical systems and of the partial transformation groupoids with applications to graph C * -algebras and semigroup C * -algebras in [224], the partial group action approach to produce a Bratteli-Vershik model linked to a minimal homeomorphism between open subsets with finite disjoint complements of the Cantor set in [179], new developments on the globalization problem for partial actions on C * -algebras and Hilbert bimodules in [168], the employment of the partial crossed product theory to the investigation of the Cuntz-Li C * -algebras related to an integral domain in [61] with a further development in [281] for C * -algebras associated with an injective endomorphism of a group with finite cokernel. Moreover, partial crossed products turned out to be useful to deal with C * -algebras arising from self-similar graph actions in [162], with C * -algebras associated to any stationary ordered Bratteli diagram in [185], as well as with ultragraph C * -algebras and related infinite alphabet shifts in [187][188][189]191]. In addition, in [212], partial coactions of C * -bialgebras, in particular of C * -quantum groups, on C * -algebras were defined and studied, and a globalization result was obtained.…”
Section: Mathematics Subject Classificationmentioning
confidence: 99%
“…The Leavitt path algebra associated with an ultragraph was defined by Imanfar, Pourabbas, and Larki in [25]. In [21], a slightly different definition appeared, and in [13] de Castro, Gonçalves and van Wyk showed that the resulting algebras are isomorphic. As in the C*-algebraic setting, the ultragraph Leavitt path algebras unify the study of Leavitt path algebras associated with graphs and the algebras associated with infinite matrices.…”
Section: Introductionmentioning
confidence: 99%